ANTI-INFLAMMATORY ACTIVITY AND CONCENTRATIONS OF POLYPHENOLS, FLAVONOIDS ETHANOL EXTRACT OF Dodonaea viscosa (SAPINDACEAE) - Necchi, Raquel Medina Martins; Ercolani, Cauriane; Dalmora, Sergio Luiz; Manfron, Melânia Palermo (Saúde (Santa Maria), 2012)
<!--[if gte mso 9]> Normal 0 21 false false false <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400;} --> <!--[endif] --> http://dx.doi.org/10.5902/223658343097 We evaluated the antiinflammatory activity of the ethanol extract of D. viscosa model in the induction of granulomatous tissue and the total content of polyphenols and flavonoids. Noting that the animals treated with the sample showed 54.46 ±3.99% inhibition of the formation of granulomatous tissue while the control group treated with nimesulide, showed 58.55 ±1.82% confirmed significant antiinflammatory activity. The measurements of total polyphenols and flavonoids in the extract were significant when compared to the standards, which confirms the popular use of this medicinal plant. Resumo: Avaliou-se a atividade antiinflamatória do extrato etanólico de D. viscosa em modelo de indução de tecido granulomatoso e o teor de polifenóis totais e flavonóides. Constatando que os animais tratados com a amostra apresentou 54,46± 3,99% de inibição da formação de tecido granulomatoso enquanto que o grupo controle tratado com nimesulida, apresentou 58,55± 1,82 % confirmando significativa atividade antiinflamatória. As dosagens de polifenóis totais e flavonóides no extrato foram significativos quando comparados aos padrões, o que comprova o uso popular desta planta medicinal.